1994
DOI: 10.1177/000331979404501104
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Impact of the Thrombolytic Era on Cardiac Rupture Complicating Acute Myocardial Infarction

Abstract: Cardiac rupture complicating acute myocardial infarction (AMI) remains a serious diagnostic and therapeutic challenge. The authors present 27 consecutive patients who died from cardiac rupture following AMI. These included 22 patients from 1975 through 1983 (prethrombolytic era) and 5 patients from 1984 through 1992 (postthrombolytic era) and all had postmortem examination. There were 16 men and 11 women with a mean age of seventy-two years. Myocardial infarction was anterior/anterolateral in 10 and inferior/i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Traditionally, factors considered to increase the risk of LVFWR would include advanced age (6 th decade or later), female gender, hypertension without left ventricular hypertrophy, delayed or no reperfusion, the anterior location of the AMI, no prior angina, a first myocardial infarction, poor collateral circulation to the infarct related area, use of NSAIDs or steroids during the acute phase, and high serum levels of C-reactive protein [3,4,10]. …”
Section: Case Presentationmentioning
confidence: 99%
“…Traditionally, factors considered to increase the risk of LVFWR would include advanced age (6 th decade or later), female gender, hypertension without left ventricular hypertrophy, delayed or no reperfusion, the anterior location of the AMI, no prior angina, a first myocardial infarction, poor collateral circulation to the infarct related area, use of NSAIDs or steroids during the acute phase, and high serum levels of C-reactive protein [3,4,10]. …”
Section: Case Presentationmentioning
confidence: 99%
“…4,5 LVFWR is 8 to 10 times more frequent than rupture of the interventricular septum or papillary muscle. 4 According to Salem et al, 15 first 5 days of AMI is the most critical period during which most cases of cardiac rupture (82%) occur. Several studies have also shown a similar finding emphasizing the early occurrence of cardiac rupture.…”
Section: Discussionmentioning
confidence: 99%
“…About 30% of the ruptures occur within the first 24‐hour postinfarction and 90% occur within the first 14 days. Risk factors include advanced age, female sex, hypertension, first myocardial infarction, and poor coronary collateral circulation 3–5 . In cases of anterior transmural acute myocardial infarction, the rupture is usually located in the anteroapical part of interventricular septum, whilst in inferior infarctions the defect occurs in its basal part 6 .…”
Section: Discussionmentioning
confidence: 99%